In Situ Observations of Aerosol Particles Remaining from Evaporated Cirrus Crystals: Comparing Clean and Polluted Air Masses - Seifert, M.; Ström, J.; Krejci, R.; Minikin, A.; Petzold, A.; Gayet, J.-F.; Schumann, U.; Ovarlez, J. (2003)
In-situ observations of aerosol particles contained in cirrus crystals are presented and compared to interstitial aerosol size distributions (non-activated particles in between the cirrus crystals). The observations were conducted in cirrus clouds in the Southern and Northern Hemisphere midlatitudes during the INCA project. The first campaign in March and April 2000 was performed from Punta Arenas, Chile (54°S) in pristine air. The second campaign in September and October 2000 was performed from Prestwick, Scotland (53°N) in the vicinity of the North Atlantic flight corridor. Size distribution measurements of crystal residuals (particles remaining after evaporation of the crystals) show that small aerosol particles (D p ‹ 0.1 μm) dominate the number density of residuals. The crystal residual size distributions were significantly different in the two campaigns. On average the residual size distributions were shifted towards larger sizes in the Southern Hemisphere. For a given integral residual number density, the calculated particle volume was on average three times larger in the Southern Hemisphere. This may be of significance to the vertical redistribution of aerosol mass by clouds in the tropopause region. In both campaigns the mean residual size increased slightly with increasing crystal number density. The form of the residual size distribution did not depend on temperature as one might have expected considering different modes of nucleation. The observations of ambient aerosol particles were consistent with the expected higher pollution level in the Northern Hemisphere. The fraction of residual particles only contributes to approximately a percent or less of the total number of particles, which is the sum of the residual and interstitial particles. Excellent agreement between the CVI and FSSP-300 probes was found supporting the assumption that each crystal is associated with only one residual particle.